Pengaruh Pendidikan dan Pengalaman terhadap Pemahaman Penumpang tentang Prosedur Keamanan di Bandar Udara Internasional Sentani - Rorong, Keny Imanuel; Fatmayati, Fryda (Ground Handling Dirgantara, 2025)
Airport security is one of the most crucial components of the aviation industry. For this reason, security screening procedures aim to avoid hazards that could threaten flight safety. However, passengers often experience difficulties in understanding security check procedures which can lead to queues and increased workload for Avsec officers. Passengers' understanding of security procedures is influenced by various factors, including the level of education and experience. This study aims to analyze the effect of education and experience on passengers' understanding of security check procedures at Sentani International Airport. This study uses a quantitative approach with a sample population of 100 respondents from airport passengers who are doing the boarding process. Based on the results of the analysis test, it shows that education and experience have a positive and significant effect on passenger understanding both partially and simultaneously. The results of these findings are expected to provide insight into the importance of education and experience in improving passenger understanding of security check procedures at airports.